Determination of Size Distributions of Concentrated Polymer Particles Embedded in a Solid Polymer Matrix - Soulé, Ezequiel Rodolfo (2008)
In this work we present the results obtained from the size characterization of polymer particles embedded in a solid polymer matrix using Static Light Scattering (SLS) and Scanning Electron Microscopy (SEM). The analyzed samples are the result of the solution polymerization of isobornyl methacrylate (IBoMA) in polyisobutylene (PIB) at complete conversion. Induced by polymerization, the system undergoes phase separation. As a result, spherical micron sized particles rich in PIB are formed. At the end of the polymerization, the particles become trapped in a solid polymer matrix rich in Poly‐IBoMA. Size, concentration, and refractive index, make the resulting particle system scatter light under the Rayleigh‐Debye‐Gans (RDG) regime with interparticle interference. For Light Scattering (LS) characterization the samples are measured with a Flat Cell Static Light Scattering (FCSLS) apparatus, in which the reaction takes place. The resulting SLS spectra are analyzed using the Percus‐Yevick approximation to model the interference effects. The local monodisperse approximation is used to consider polydispersity in the particle sizes. The estimated particle size distributions agree well with the measurements from SEM. In this work a concentrated particle system that naturally scatters light according to the RDG regime has been fully characterized in terms of its particle size distribution. This work, against the opinion of other authors, shows the feasibility of measuring still particles using a one dimensional array of light detectors.